Dampak Penerapan Kebijakan Tanggung Jawab Sosial dan Lingkungan (TJSL) Berbasis Pemberdayaan Masyarakat PT Kilang Pertamina Internasional RU IV Cilacap - Shodikin, King Amil Hamzah Al Hakim; Aziz, Abdul; Rahmawati, Puji; Fitriati, Rizky; Supriyatna, Cecep (Yayasan Sagita Akademia Maju, 2025)
Discussion related to the implementation of a company's Tanggung Jawab Sosial dan Lingkungan (TJSL) policy is often considered as a charity activity and does not have a significant sustainable impact. The Empowerment-based TJSL program is one option in implementing the TJSL program to have a more positive impact. This research is qualitative research with descriptive analysis. Primary data was obtained through field observations and interviews, while secondary data was obtained from relevant documents. The results of the study indicate that there is an impact of the implementation on the social, natural, economic and well-being dimensions. In the social dimension, a decrease in poverty rates of 0.26% has been achieved and four new groups have been formed that are involved in program activities. In the natural dimension, mangrove conservation efforts through planting 25,000 tree seedlings on 5.5 hectares of land have resulted in a CO₂ storage impact of 13,958.96 tons per year. The economic aspect contributes to increasing group income by Rp13,650,000 per month. From the welfare dimension, two practical guidebooks have been prepared as a reference for the community to understand the mangrove ecosystem and fisheries cultivation and make the program location a centre of excellence for other institutions to learn.